noop_090-ath - Ilia-Georgiadou, Ifigeneia; Kalogerias, Angelos (Design/Arts/Culture, 2025)
"noop_090-ath" is a vibrant art fanzine that captures the essence of 90s nostalgia through a unique blend of urban diary photographs, evocative poems, and reflective texts. Each issue immerses readers in the raw energy of the decade, showcasing candid snapshots of city life—graffiti-covered walls, bustling streets, and intimate moments that resonate with collective memory. With its aesthetic, "noop_090-ath" serves as both a tribute to the past and a canvas for contemporary voices, creating a bridge between eras and inviting a dialogue as each reader experiences it with their own eyes.